EWSR1-NFATC2 Translocation-associated Sarcoma Clinicopathologic Findings in a Rare Aggressive Primary Bone or Soft Tissue Tumor. (August 2019) - Wang, Grace Y.; Thomas, Dafydd G.; Davis, Jessica L.; Ng, Tony; Patel, Rajiv M.; Harms, Paul W.; Betz, Bryan L.; Schuetze, Scott M.; McHugh, Jonathan B.; Horvai, Andrew E.; Cho, Soo-Jin; Lucas, David R.
Abstract : In recent years, a novel small round cell sarcoma harboring EWSR1-NFATC2 translocation with immunomorphologic overlap with Ewing sarcoma (ES), myoepithelial tumors, and extraskeletal myxoid chondrosarcoma has emerged. There has not been a case series devoted to describing its detailed clinicopathologic and immunohistochemical characteristics. Six sarcomas harboring EWSR1-NFATC2 fusion transcripts by reverse transcription polymerase chain reaction and amplification of the fusion gene by fluorescence in situ hybridization were identified. The patients were 5 adult men and 1 adult woman. Three were primary bone tumors of the radius and 3 were primary soft tissue tumors. Most tumors showed monomorphic round to epithelioid cells in anastomosing cords and abundant myxohyaline to collagenous extracellular matrix. Two tumors had large areas of a solid, matrix-poor histomorphology. All tumors stained for CD99 and NKX2.2; while EMA, dot-like cytokeratin, and focal WT-1 and SMA were present in some tumors. All but 1 tumor showed poor histologic and radiologic responses to neoadjuvant ES-specific chemotherapy. Local or distant recurrences happened in 4 cases. EWSR1-NFATC2 sarcoma is a novel translocation-associated sarcoma. It presents as either a primary bone or soft tissue tumor, usually exhibits distinctive histopathologic features, and has predilection for long bones of adult men. It consistently shows recurrent fusion gene amplification readily detectable by EWSR1 breakapart fluorescence in situ hybridization, which serves as a diagnostic surrogate. It has potential for local and distant recurrence and histologic progression, and is resistant to Ewing sarcoma-specific chemotherapy.